Review on Business Intelligence - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Due to the rapid growth of new technologies, the Business Intelligence (BI) market is growing as well that forces the corporations to adopt their offerings to the needs of the customer. The implementation of the business intelligence program has become one of the most important technical and operational advances in corporate organizations encouraging the diffusion of knowledge, the foundation of decision-making processes in industry. Since the integrated the implemented way of BI is quite different among organizations, it is important to approach BI literature through the adaptation and implementation of BI application, BI architects, and enabling factors in BI projects. In addition, this paper will also discuss how technological capabilities such as user access, data quality and BI integration with other systems within the company, as well as organizational capabilities such as support for flexibility and risk management, are essential to BI success, regardless of the decision environment. Last but not least, this paper will also examine how the concept of BI on the school of thought was built up. This paper expects results to build the interest and feedback for organizations looking to incorporate a BI program in their organization.